Estrogen use and early onset Alzheimer's disease: a population-based study - Slooter, A. (BMJ Group, 1999)
Estrogen use may be protective for Alzheimer's disease with late onset. However, the effects on early onset Alzheimer's disease are unclear. This issue was studied in a population based setting. For each female patient, a female control was matched on age (within 5 years) and place of residence. Information on estrogen use and other risk factors were, for cases (n=109) and controls (n=119), collected from the next of kin by structured interview. The strength of the association between estrogen use and early onset Alzheimer's disease was studied using conditional logistic regression with adjustment for age and education level. There was an inverse association between estrogen use and early onset Alzheimer's disease (adjusted odds ratio 0.34; 95% confidence interval 0.12-0.94). The study therefore suggests that estrogen use is beneficial to Alzheimer's disease with early onset.